2013
DOI: 10.1097/qad.0b013e32835fab77
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunological responses to human mesenchymal stem cell therapy in difficult-to-treat HIV-1-infected patients

Abstract: Objective HAART largely decreases morbidity and mortality in chronic HIV-1-infected patients, but immune nonresponders (INRs) with full viral suppression still fail to reverse the immune deficiency. This study evaluated the safety and immunological responses of human umbilical cord mesenchymal stem cell (MSC) therapy in HIV-1-infected INRs. Design and Methods A total of 13 HIV-1-infected INRs were enrolled in this pilot prospectively open-labeled controlled clinical trial. Seven patients were administered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 40 publications
3
66
0
1
Order By: Relevance
“…Our results agree with recent findings showing that persistent IFN-I signaling plays a detrimental role during chronic lymphocytic choriomeningitis virus infection and that blockade of IFN-I signaling by IFNAR antibody could reverse T cell exhaustion and enhance antiviral immune response (3,4). The IFNAR blocking antibody will thus facilitate novel therapeutic development aimed at those difficult-to-treat HIV-1-infected patients with sustained IFN-I signaling during cART (23,24,40). HIV-1 reservoirs are refractory to antiretroviral therapies (ART) and remain the major barrier to curing HIV-1 (34,35).…”
Section: Discussionsupporting
confidence: 91%
“…Our results agree with recent findings showing that persistent IFN-I signaling plays a detrimental role during chronic lymphocytic choriomeningitis virus infection and that blockade of IFN-I signaling by IFNAR antibody could reverse T cell exhaustion and enhance antiviral immune response (3,4). The IFNAR blocking antibody will thus facilitate novel therapeutic development aimed at those difficult-to-treat HIV-1-infected patients with sustained IFN-I signaling during cART (23,24,40). HIV-1 reservoirs are refractory to antiretroviral therapies (ART) and remain the major barrier to curing HIV-1 (34,35).…”
Section: Discussionsupporting
confidence: 91%
“…Their results showed that MSCs as an adjunct therapy are safe and can now be explored further for the treatment of patients with MDR or XDR tuberculosis in combination with standard drug regimens [188]. The data suggested that MSCs transplantation may be used as a novel immunotherapeutic approach to reversing immune deficiency in HIV-1-infected INRs [190] .…”
Section: Mscs and Inflammatory Diseasementioning
confidence: 99%
“…An interesting clinical study has shown that UC-MSCs increase their circulating naive and central memory CD4 T-cell numbers and restore HIV-specific IFN-␥ and IL-2 production. In these patients there is systemic immune reactivation [55].…”
Section: Retrovirusesmentioning
confidence: 99%